Nearly free silanols drive the interaction of crystalline silica polymorphs with membranes: Implications for mineral toxicity - Pavan, Cristina; Escolano-Casado, Guillermo; Bellomo, Chiara; Cananà, Stefania; Tomatis, Maura; Leinardi, Riccardo; Mino, Lorenzo; Turci, Francesco (Frontiers in Chemistry, 2023)
Crystalline silica (CS) is a well-known hazardous material that causes severe diseases including silicosis, lung cancer, and autoimmune diseases. However, the hazard associated to crystalline silica is extremely variable and depends on some specific characteristics, including crystal structure and surface chemistry. The CS polymorphs share the SiO2 stoichiometry and differentiate for crystal structure. The different crystal lattices in turn expose differently ordered hydroxyl groups at the crystal surface, i.e., the silanols. The nearly free silanols (NFS), a specific population of weakly interacting silanols, have been recently advanced as the key surface feature that governs recognition mechanisms between quartz and cell membrane, initiating toxicity. We showed here that the NFS occur on the other CS polymorphs and take part in the molecular interactions with biomembranes. A set of CS polymorphs, including quartz, cristobalite, tridymite, coesite, and stishovite, was physico-chemically characterized and the membranolytic activity was assessed using red blood cells as model membranes. Infrared spectroscopy in highly controlled conditions was used to profile the surface silanol topochemistry and the occurrence of surface NFS on CS polymorphs. All CS polymorphs but stishovite were membranolytic. Notably, pristine stishovite did not exhibited surface NFS. The topochemistry of surface silanols was modulated by thermal treatments, and we showed that the occurrence of NFS paralleled the membranolytic activity for the CS polymorphs. These results provide a comprehensive understanding of the structure-activity relationship between NFS and membranolytic activity of CS polymorphs, offering a possible clue for interpreting the molecular mechanisms associated with silica hazard and bio-minero-chemical interfacial phenomena, including prebiotic chemistry.